VI International Scientific Seminar “Hagiography in the Russian Cultural Space: on the 200th Anniversary of Fedor Dostoevsky’s Birth” - Lyudmila G. Dorofeeva (Слово.ру: балтийский акцент, 2022)
The article provides an overview of the VI International Scientific Seminar "Hagiography in the Russian Cultural Space", dedicated to the 200th anniversary of Fedor Dostoevsky’s birth. The seminar was organized at the Immanuel Kant Baltic Federal University on October 11—12, 2021. The main ideas and key points of the presentations of the plenary and section meetings are explored.